Breastfeeding and the risk of rotavirus diarrhea in hospitalized infants in Uganda: a matched case control study - Kalyango Joan N; Karamagi Charles K; Bachou Hanifa; Wobudeya Eric; Mutebi Edrisa; Wamani Henry (BMC, 2011)
Abstract Background Rotavirus is responsible for over 25 million outpatient visits, over 2 million hospitalizations and 527,000 deaths annually, worldwide. It is estimated that breastfeeding in accordance with the World Health Organization recommendations would save 1.45 million children's lives each year in the developing countries. The few studies that examined the effect of breastfeeding on rotavirus diarrhea produced conflicting results. This study aimed to determine the effect of breastfeeding on rotavirus diarrhea among admitted infants in Uganda. Methods The study was conducted in the Pediatrics medical emergency unit of a National Referral hospital during a peak incidence time for rotavirus from February to April 2008. It was an age matched case-control study with a ratio of 1:1. We consecutively enrolled infants presenting at the study site during this period whose caretakers consented to participate in the study. A minimum sample size of 90 pairs was adequate with power of 80% to detect a 30% decrease in breastfeeding rate among the cases assuming a breastfeeding rate of 80% in the controls. The infants with rotavirus positive results were the "cases". We used the commercial enzyme immunoassay kit (DAKO IDEIA™ rotavirus EIA detection kit) to diagnose the cases. The "controls" were admitted children with no diarrhea. We compared the cases and controls for antecedent breastfeeding patterns. Results Ninety-one matched case-control age-matched pairs with an age caliper of one month were included in the analysis. Breastfeeding was not protective against rotavirus diarrhea (OR 1.08: 95% CI 0.52 - 2.25; p = 0.8) in the conditional logistic model. Conclusions Our study findings did not reveal breastfeeding as protective against rotavirus diarrhea in infants. This suggests searching for other complementary preventive methods such as rotavirus vaccination and zinc supplementation to reduce the problem of rotavirus diarrhea in infants irrespective of their feeding practices.